2017
DOI: 10.1016/j.ecoenv.2016.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of aerobic and anaerobic biodegradation of methylparaben and propylparaben in activated sludge

Abstract: The biodegradability of two typical parabens (methylparaben and propylparaben) in activated sludge, at initial concentrations of 1mgL or 10mgL, was investigated under aerobic and anaerobic conditions. The results showed that microorganisms played a key role in degradation of parabens in WWTPs, especially in aerobic systems. The half-lives of methylparaben and propylparaben under aerobic conditions have been estimated to range between 15.8 and 19.8min, and benzoic acid was found to be one of the major biodegrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Adsorption is an interesting alternative to other tertiary water treatments such as chlorination, advanced oxidation and ozonation when the molecules are reactive (as methylparaben) and can form toxic compounds, such as dioxins, organochlorine compounds and chloroamines upon oxidation [8,9,10]. Adsorption processes strictly depends on physical (e.g., surface area and pore volume of the adsorbent, molecular size of the adsorbate, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption is an interesting alternative to other tertiary water treatments such as chlorination, advanced oxidation and ozonation when the molecules are reactive (as methylparaben) and can form toxic compounds, such as dioxins, organochlorine compounds and chloroamines upon oxidation [8,9,10]. Adsorption processes strictly depends on physical (e.g., surface area and pore volume of the adsorbent, molecular size of the adsorbate, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…This interpretation is consistent with the findings published by Ilyas and Hullebusch (2020), who confirmed the higher potential of aerobic degradation for AC at CWs. Likewise, Wu et al (2017) reported that MP exhibited comparatively higher persistence in anaerobic treatment systems compared to aerobic systems and they confirmed that the majority of parabens can be removed by aerobic biodegradation whereas minor removal is possible in anaerobic systems. Furthermore, Anjos et al (2018) mentioned that the degradation process almost related to length of carbon chain, which explains the high degradation of the short chain MP compound, particularly under aerobic conditions.…”
Section: Resultsmentioning
confidence: 66%
“…This interpretation is consistent with the findings published by Ilyas and Hullebusch (2020) , who confirmed the higher potential of aerobic degradation for AC at CWs. Likewise, Wu et al. (2017) reported that MP exhibited comparatively higher persistence in anaerobic treatment systems compared to aerobic systems and they confirmed that the majority of parabens can be removed by aerobic biodegradation whereas minor removal is possible in anaerobic systems.…”
Section: Resultsmentioning
confidence: 66%
“…Its extensive use as a fungicide and preservative has led to ubiquitous dispersal in the environment (Haman et al ). Despite its degradability by microbes, methylparaben is reported to resist degradation during wastewater treatment and is then released in the treated effluent (Hernández Leal et al ; Wu et al ). To our knowledge, this is the first identification of a methylparaben metabolite under sulfate‐rich and methanogenic conditions, although biodegradation has been suggested by reports of biogas production in methanogenic communities spiked with methylparaben (Madsen et al ; Haman et al ).…”
Section: Discussionmentioning
confidence: 99%